The Relationship between Gynecological Cancer Awareness and Self-Care Agency in Married Women - Dal, Nursel Alp; Beydag, K. Derya; Oner, Ozlem Ikde (Georg Thieme Verlag Kg, 2023)
Objective This study was conducted to determine the relationship between gynecological cancer awareness and self-care agency among married women. Materials and Methods This descriptive and cross-sectional study was performed with 819 women who presented to the obstetrics polyclinic of a hospital located in the west of Turkey between December 15, 2020 and April 15, 2021. The data of the study were collected by using the Exercise of Self-Care Agency Scale (ESCA) and the Gynecological Cancers Awareness Scale (GCAS). Results The mean age of the participants was 37.62 +/- 9.181 years. The mean ESCA score of the women who participated in this study was 95.89 +/- 25.060, which indicated moderate levels of self-care agency. The mean total GCAS score of the participants of this study was 156.57 +/- 32.930, which indicated high levels of gynecological cancer awareness among the women. As the self-care agency of the women increased, their awareness of gynecological cancers also increased. Conclusion Midwives and nurses who provide preventive and supportive healthcare services may affect the self-care agency of women positively by gynecological cancer awareness they will raise in these women.
Keywords: gynecological cancer; awareness; self-care; self-care agency